2008
DOI: 10.1142/s0218127408021257
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Multistability by Small Periodic Perturbation

Abstract: A small perturbation of any system parameters may not in general create any significant qualitative change in dynamics of a multistable system. However, a slow-periodic modulation with properly adjusted amplitude and frequency can do so. In particular, it can control the number of coexisting attractors. The basic idea in this controlling mechanism is to introduce a collision between an attractor with its basin boundary. As a consequence, the attractor is destroyed via boundary crisis, and the chaotic transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…Multistate switching devices are needed for the next generation of all-optical computing and communication [13]. The multistability phenomenon is observed for many nonlinear systems and the transition of complex multistability to controlled monostability has raised a lot of attention [14,15]. For Vertical-Cavity Surface-Emitting Lasers (VCSELs) with the PROF setup, it was recently shown that a second weak feedback allows generation of robust SWs with respect to parameter changes [10].…”
mentioning
confidence: 99%
“…Multistate switching devices are needed for the next generation of all-optical computing and communication [13]. The multistability phenomenon is observed for many nonlinear systems and the transition of complex multistability to controlled monostability has raised a lot of attention [14,15]. For Vertical-Cavity Surface-Emitting Lasers (VCSELs) with the PROF setup, it was recently shown that a second weak feedback allows generation of robust SWs with respect to parameter changes [10].…”
mentioning
confidence: 99%
“…The exception, of course, is a perturbation in the values of the variables that preserves the value of the conserved quantity, for example, a perturbation that changes y 1 and y 2 equally in Eqs. (3), so that the value of the conserved quantity C remains the same. However, this argument does not apply to the system described by Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs in two subsystems with an intermediate from each subsystem involved in the other subsystem, comparable to the model (R 7 )-(R 18 ) described by Eqs. (3). In the course of the conversion, two products, C and D, are formed that do not participate in the dynamics, as well as the main product E. We therefore do not include the time evolution of these species in deriving system (A1), below.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, controlling multistability [8] related nonlinear phenomena have become an important direction of applied research in Nonlinear Science [9]. In particular, suitable small-periodic perturbation has been found to be very efficient in order to reduce the number of coexisting attractors.…”
Section: Introductionmentioning
confidence: 99%